2019
DOI: 10.5771/0949-6181-2019-2-280
|View full text |Cite
|
Sign up to set email alerts
|

CSR reporting practice: Is there room for integration? – Evidence from Serbian foreign investors

Abstract: Despite the efforts of companies to invest into CSR reporting and to communicate information to various stakeholders these efforts in Serbia are still at a very low level compared with the developed countries. In this study content analysis is conducted on a sample of companies comprising the list of all investors in Serbia investing more than 100 million € and classified into Privatization M&A and Greenfield investors. CSR disclosure index and Integration index are created and correlation has been establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To assess the level of Corporate Social Disclosure (CSD) quality of the banks, we used the slightly corrected CSR Index developed by Montecchia et al (2016, p. 46), recently used by Knežević and Pavlović (2019), which is named EESGI (Environmental, Economic, Social, Governance index). Table 2 shows the variables used in the creation of this index.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the level of Corporate Social Disclosure (CSD) quality of the banks, we used the slightly corrected CSR Index developed by Montecchia et al (2016, p. 46), recently used by Knežević and Pavlović (2019), which is named EESGI (Environmental, Economic, Social, Governance index). Table 2 shows the variables used in the creation of this index.…”
Section: Methodsmentioning
confidence: 99%
“…CSR in Serbia is more focused in the area of non-financial philanthropy and humanitarian activities, and companies consider it important for the business (Mijatović, et al, 2015). The CSR index and its relation with the integrated reporting in Serbia has been in the centre of research conducted by Knežević and Pavlović (2019). These researchers found that the integration of financial and non-financial information in financial and sustainability reports of Serbian companies is at a very low level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the fact that the level of non-financial reporting in Serbia is still low [49], in the field of WEEE recycling, the quantity of products recycled during the year is available, since all companies submit accurate reports, as the basis for obtaining government incentives. These reports are periodically published by the Environmental Protection Agency, and in the period 2011-2018, the quantity of recycled e-products ranged between 7084 t and even 37,004 t, with the maximum volume of recycling reached in 2016 [46] (p. 35).…”
Section: Socio-economic and Institutional Environment In The Republicmentioning
confidence: 99%